A Novel SimpleDrop Chip for 3D Spheroid Formation and Anti-Cancer Drug Assay - Liu, Xiaoli; Lin, Huichao; Song, Jiaao; Zhang, Taiyi; Wang, Xiaoying; Huang, Xiaowen; Zheng, Chengyun (Micromachines (Basel), 2021)
Cell culture is important for the rapid screening of anti-cancer drug candidates, attracting intense interest. Traditional 2D cell culture has been widely utilized in cancer biological research. However, 3D cellular spheroids are able to recapitulate the in vivo microenvironment of tissues or tumors. Thus far, several 3D cell culture methods have been developed, for instance, the hanging drop method, spinner flasks and micropatterned plates. Nevertheless, these methods have been reported to have some disadvantages, for example, medium replacement is inconvenient or causes cellular damage. Here, we report on an easy-to-operate and useful micro-hole culture chip (SimpleDrop) for 3D cellular spheroid formation and culture and drug analysis, which has advantages over the traditional method in terms of its ease of operation, lack of shear force and environmentally friendliness. On this chip, we observed the formation of a 3D spheroid clearly. Three drugs (paclitaxel, cisplatin and methotrexate) were tested by both cell viability assay and drug-induced apoptotic assay. The results show that the three drugs present a similar conclusion: cell viability decreased over time and concentration. Moreover, the apoptotic experiment showed a similar trend to the live/dead cell assay, in that the fraction of the apoptotic and necrotic cells correlated with the concentration and time. All these results prove that our SimpleDrop method is a useful and easy method for the formation of 3D cellular spheroids, which shows its potential for both cell–cell interaction research, tissue engineering and anticancer drug screening.